Corporate social responsibility and firm performance: evidence from manufacturing companies in Sri Lanka - Kengatharan, L.; Jeyan Suganya, D.F.; Sulochani, R.G.R. (Faculty of Management Studies & Commerce, University of Jaffna, 2020)
Each sector faces high demand for Corporate Social Responsibility (CSR) to maximise share holders wealth for recent decades. The purpose of this study is to examine the impact of CSR on firm performance of manufacturing companies listed on Colombo Stock Exchange in Sri Lanka. In order to carry out this study 31 listed manufacturing companies were selected as sample among 40 companies. CSR activities are considered as explanatory variables which are divided into three dimensions such as economic, social and environmental activities. Tobin's Q is used to measure firm performance while firm size and financial leverage are treated as control variables. Necessary data for this study were collected from financial statements of the respective companies for the period of five years from 2013 to 2018. Multiple regression analysis is used to test hypotheses to examine the impact of CSR on firm performance. The results of regression model reveals that there is a significant negative impact of economic activities, social activities and environmental activities on Tobin's Q. Finding of the study suggests that management of the company should focus more on CSR practices to attract more customers towards their product and it can increase firm value and shareholders' wealth of the firm in future. When the investors prefer the companies which have more consideration on CSR to invest their money, they can make higher earnings on their investment.
Keywords: Economic activities; Environmental activities; Firm performance; Social activities; Tobin q